1976
DOI: 10.1136/hrt.38.7.725
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmias in two patients with left ventricular bypass transplants.

Abstract: Two patients who underwvent left ventricular bypass transplants are described. Both patients sustained postoperative rhythm disturbances of their own hearts during sinus rhythm of the donor hearts. Illustrative examples of atrial flutter, ventricular flutter, ventricular fibrillation, blocked atrial extrasystoles, and double ventricular parasystole in the recipient hearts are presented. The patients tolerated all these arrhythmias well during uninterrupted sinus rhythm in the donor heart. The problems in inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

1979
1979
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 1 publication
0
4
0
2
Order By: Relevance
“…Nonetheless, most VAs in HHTx are related to the underlying recipient heart disease 9 and are clinically challenging because the recipient heart often remains functionally important. HHTx, which was originally performed as a biological LV assist device, 10 evolved into a biventricular assist configuration after the report of 2 patients who experienced heart failure related to recipient heart ventricular fibrillation 11 . In the later configuration, recipient VAs are often well tolerated and their diagnosis requires careful physical examination searching for the disappearance of the irregular pulse pattern related to donor heart parasystole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, most VAs in HHTx are related to the underlying recipient heart disease 9 and are clinically challenging because the recipient heart often remains functionally important. HHTx, which was originally performed as a biological LV assist device, 10 evolved into a biventricular assist configuration after the report of 2 patients who experienced heart failure related to recipient heart ventricular fibrillation 11 . In the later configuration, recipient VAs are often well tolerated and their diagnosis requires careful physical examination searching for the disappearance of the irregular pulse pattern related to donor heart parasystole.…”
Section: Discussionmentioning
confidence: 99%
“…HHTx, which was originally performed as a biological LV assist device, 10 evolved into a biventricular assist configuration after the report of 2 patients who experienced heart failure related to recipient heart ventricular fibrillation. 11 In the later configuration, recipient VAs are often well tolerated and their diagnosis requires careful physical examination searching for the disappearance of the irregular pulse pattern related to donor heart parasystole. Discrimination of the 2 superimposed rhythms on standard 12-lead ECG can be difficult, and some authors used echocardiography to identify which heart was concerned by the arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…He remained well for four months, when he experienced the first of several attacks of paroxysmal ventricular tachycardia of his own heart, requiring electrical defibrillation and drug treatment. 5 In May 1976 he was admitted with bacterial endocarditis due to Staphylococcus aureus. He then suffered an acute myocardial infarction in his own heart.…”
Section: Casementioning
confidence: 99%
“…The use of pacemaker systems in heterotopic heart transplantation 16,17 Experimental studies showed that with synchronous pacing of both hearts the extensively damaged recipient ventricle failed to open the aortic valve. It follows, therefore, that some stasis will occur within this dilated left ventricle with the subsequent possibility of thrombus formation.…”
Section: Clinical Studiesmentioning
confidence: 99%